Bigger ships in the world, one more challenge for Brazil: an analysis about the national dredging program - Menegazzo, Luciano; Petterini, Francis (Estudos Econômicos (São Paulo), 2018)
The cargo ships have grown in size, while there was a lacking of maintaining of the Brazilian waterways. Therefore, it is common wait the rising tide to safely conduct the ships, which implies in demurrage costs. The article analyzes the impact of the National Dredging Program, which aims to mitigate the problem. Using the methodology of synthetic controls to model the ship handling in 11 ports treated, with 24 comparative units, we met indicatives that the program caused impact on 4 of them. The conclusion is that the program is strategic for foreign trade, but needs to be improved.